2015
DOI: 10.2298/pif1503161k
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of insect pollinators with reference to their impact on yield production of canola (Brassica napus L.) in Ismailia, Egypt

Abstract: SUMMARYA study of insect pollinators and their impact on canola yield was conducted during the 2013/2014 and 2014/2015 growing seasons. The study was carried out at an experimental farm, Faculty of Agriculture, Suez Canal University, Ismailia. The results revealed that 21 species of insect pollinators belonging to 14 families under four orders visited canola flowers. The abundance of Hymenoptera insects reached the maximum of 67.90%, followed by Diptera 14.97%, Coleoptera 13.61%, then Lepidoptera 2.26% as aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
3
7
0
Order By: Relevance
“…The results of the present investigation also corroborate the observations made by Singh and Singh (1992) who reported that insectpollinated plots produced three times heavier seed then self-pollinated plants in B. campestris. The present findings also supported the results of Kamel et al (2015) who observed that the weight of 1000 seeds was higher in open-pollinated plants (3.13 g) than those of caged plants (2.4 g) in B. napus.…”
Section: Fig 3 Mean+se Comparison Of Different Crop Yielding Parasupporting
confidence: 93%
“…The results of the present investigation also corroborate the observations made by Singh and Singh (1992) who reported that insectpollinated plots produced three times heavier seed then self-pollinated plants in B. campestris. The present findings also supported the results of Kamel et al (2015) who observed that the weight of 1000 seeds was higher in open-pollinated plants (3.13 g) than those of caged plants (2.4 g) in B. napus.…”
Section: Fig 3 Mean+se Comparison Of Different Crop Yielding Parasupporting
confidence: 93%
“…Open pollination increased pod number by 6.68%, seed number per pod by 10.10%, thousand kernel weight by 13.35%, oil rate by 4.63% and oil yield by 80.09% compared with caged without bee. Similar findings were documented for canola (Sabbahi et al, 2005;Manning and Wallis, 2005;Munawar et al, 2009;Harrad et al, 2015;Kamel et al, 2015). The statistically lowest plant height and partially branch number obtained from open pollination compared with caged plots revealed that cage material can show a shading effect on plant that prevents light quality and promotes vegetative growth.…”
Section: Resultssupporting
confidence: 77%
“…Similarly, Oz et al (2008) found that honeybee pollination increased the seed yield significantly but not protein and oil percentage in seeds of winter rapeseed. The important increases observed in 31.9% of seeds per plant (Mussury and Fernandes, 2000), 34.5% of seed weight (Williams et al, 1986;Adegas and Nogueira-Couto, 1992), 15.54% of the number of pods per plant and 33.5% of seed yield per plant (Harrad et al, 2015), 30.4% of thousand kernel weight (Kamel et al, 2015) when compared to autogamy conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To an efficient pollination process, it is necessary to the floral visitor to present specific morphological and behavioral characteristics for each type of flower [1]. This is the case of Apis mellifera honeybees that have been identified as effective canola pollinators in different parts of the world [7;11;12].…”
Section: Introductionmentioning
confidence: 99%
“…In canola cultivation, species of Halictus sp. [8], Bombus lapidarius [14], and Colletes lacunatus [11] bees were identified as alternative pollinators. In Brazil, the stingless bee species Trigona spinipes was identified with a potential pollinator for canola [15].…”
Section: Introductionmentioning
confidence: 99%